Perlindungan Data Pribadi Di Indonesia: Analisis Undang-Undang Dan Fiqh Siyasah Dusturiyah - Yusmahendra, Denny; Hakim, Dani Amran (IAIN Metro, 2025)
Uncontrolled disclosure of personal data has been proven to pose many risks of various criminal acts. Such as bullying, threats, fraud, and account hacking are unavoidable. The importance and urgency of the issue of personal data protection is increasingly being highlighted by the Indonesian government following the rise in cases of personal data leakage in Indonesia. Therefore, the Indonesian government passed Law Number 27 of 2022 concerning Personal Data Protection. This type of research is library research. This research is descriptive analysis using qualitative methods. The data source in this research is a secondary data source obtained through documentation. through article 65 of the Personal Data Protection Law, it provides new hope for the security of people's personal data in Indonesia and as a trigger for the habits of Indonesian people to be more careful in giving or using their own or other people's data, and prohibits everyone from using personal data. other people with the aim of misusing the data, either to benefit themselves or for other interests. Article 65 of the Personal Data Protection Law is in line with fiqh siyasah dusturiyah. Based on Surah an-Nur verse 27, Ibn Asyur stated that the house is the most private place, not just a place to shelter from the heat, take shelter when it rains, warm oneself in cold weather. Discusses state laws and regulations in terms of which regulations are for the benefit of citizens in order to achieve the principle of fulfilling citizens' rights. Because providing protection for personal data is one manifestation of fulfilling the rights of every citizen.